2013
DOI: 10.1155/2013/729413
|View full text |Cite
|
Sign up to set email alerts
|

CD59 Underlines the Antiatherosclerotic Effects of C-Phycocyanin on Mice

Abstract: The effects of C-phycocyanin (C-PC) on atherosclerosis and the regulatory effects of CD59 gene on anti-atherosclerotic roles of C-PC were investigated. Apolipoprotein E knockout (ApoE(−/−)) mice were randomly divided into four groups: control group, C-PC treatment group, CD59 transfection group and C-PC+CD59 synergy group. The mice were fed with high-fat-diet and treated with drug intervention at the same time. Results showed the atherosclerotic mouse model was successfully established. CD59 was over-expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Phycocyanin significantly decreases HeLa cells multiplication in comparison to control cells (Li et al, 2006 , 2013 ; Yang et al, 2014 ). Furthermore, it activates the apoptotic pathway, including cell shrinkage in HeLa cell lines.…”
Section: Arthrospira Human Health and Medicine—the Multipmentioning
confidence: 99%
See 1 more Smart Citation
“…Phycocyanin significantly decreases HeLa cells multiplication in comparison to control cells (Li et al, 2006 , 2013 ; Yang et al, 2014 ). Furthermore, it activates the apoptotic pathway, including cell shrinkage in HeLa cell lines.…”
Section: Arthrospira Human Health and Medicine—the Multipmentioning
confidence: 99%
“…This activity prevents smooth muscle cell proliferation and the apoptosis of endothelial cells, reducing blood fat levels. In consequence, C-phycocyanin inhibits the development of atherosclerosis (Li et al, 2013 ). The GLA present in Arthrospira reduces cholesterol accumulation in the hypolipidemic nephrotic syndrome (Samuels et al, 2002 ).…”
Section: Arthrospira Human Health and Medicine—the Multipmentioning
confidence: 99%
“…The lipid-lowering and antioxidant effects of C-PC suggest its roles in CVD prevention and atherosclerotic formation. Li [ 128 ] found that C-PC can inhibit the progress of atherosclerosis, and the antiatherosclerotic effects of C-PC might be enhanced by promoting CD59 expression, preventing smooth muscle cell proliferation and endothelial cell apoptosis, reducing blood fat levels, and inhibiting the development of atherosclerosis.…”
Section: Antioxidationmentioning
confidence: 99%
“…Increased vascular expression and activity of NADPH oxidase is a feature of metabolic syndrome and a mediator of the associated endothelial dysfunction 90–93. Ingestion of spirulina or phycocyanin has been found to exert anti-atherosclerotic effects in rodent models 94–97…”
Section: Bilirubin Directly Protects Tissues Targeted By Metabolic Symentioning
confidence: 99%